Experimental study of engine performance and emission of palm, mustard and calophyllum biodiesel blends in a diesel engine / Sanjid Ahmed Patwary - Sanjid Ahmed , Patwary (2015)
Present energy situation of the world is unsustainable due to unequal geographical distribution of natural wealth as well as environmental, geopolitical and economical concerns. Ever increasing drift of energy consumption due to growth of population, transportation and luxurious lifestyle has motivated researchers to carry out research on biofuels as a sustainable alternative fuel for diesel engine. Biodiesel seems as one of the best choices among other alternative fuel sources due to its renewability, cost effectiveness and reduction of pollutants in exhaust gas emission which are promoting biofuels as a suitable substitute of diesel fuel in near future. This research endeavor aims to produce and evaluate the comparative performance and emission of palm, mustard and Calophyllum inophyllum biofuels in a four cylinder diesel engine. This was followed by the production of palm, mustard and Calophyllum inophyllum biodiesel from their respective oils and blending them with diesel fuel. Detailed characterization of physicochemical properties of pure biodiesel and their blends meet standard ASTM specifications. Engine performance and emission were evaluated by measuring brake specific fuel consumption (BSFC), brake thermal efficiency (BTE), engine power, engine torque, carbon monoxide (CO), hydrocarbon (HC), and nitric oxide (NO) emission. The results of engine performance revealed that biodiesel blended fuels produced average reduction in engine BTE, power and torque with increased BSFC. In case of engine emission, biodiesel blends showed an average reduction in CO and HC with a slight increase in NO & CO2 emission. Overall, Calophyllum inophyllum biodiesel blends showed better engine performance and emission compared to palm and mustard biodiesel blends. The peak cylinder pressure and heat release of biodiesel blends were found higher and closer to top dead centre compared to diesel fuel. This is due to the shorter ignition delay and higher cetane number of biodiesel. In conclusion, palm, mustard and Calophyllum inophyllum are potential feedstock for biodiesel production and up to 20% of their blends could be used in the diesel engine without any modification. Besides, as producing biofuel from edible oil source has received criticism worldwide, therefore using non-edible vegetable oils like: calophyllum as biofuel can replace the current dependence on the edible oil source.